How to be a woman online : surviving abuse and harassment, and how to fight back - Jankowicz, Nina (Bloomsbury Academic, 2022)
"When Nina Jankowicz's first book on online disinformation was profiled in The New Yorker last year, she expected attention but not an avalanche of abuse and harassment, predominantly from men, online. All women in politics, journalism and academia now face untold levels of harassment and abuse in online spaces. Together with the world's leading extremism researchers, Jankowicz wrote one of the definitive reports on this troubling phenomenon. Drawing on rigorous research into the treatment of Kamala Harris - the first woman vice-president - and other political and public figures, Nina also uses on her own experiences to provide a step-by-step plan for dealing with harassment, abuse, doxing and disinformation in online spaces. The result is a must-read for researchers, journalists and all women with a profile in the online space"--